A comprehensive theoretical and experimental study on structural and mechanical properties of Si doped ZnO. (1st July 2017) - Bajpai, Gaurav; Srivastava, Tulika; Nasir, Mohd; Tiwari, Saurabh; Bajpai, Shubhra; Rini, E.G.; Biring, Sajal; Sen, Somaditya
Abstract: Si 4 + is a smaller ion with higher charge compared to Zn 2 + . When incorporated in ZnO lattice, above a certain amount, the Si 4 + ions create defects at the substituted sites. The Zn and O planes are dragged closer to each other by Si substitution while the lattice expansion along c-axis is more than that along a or b axes. However, the c/a ratio decreases continuously. The mechanical property deteriorates with substitution as well at par with the structural changes. Experimentally observed mechanical hardness of Si 4 +  substituted ZnO pellets decrease with incorporation of Si following the theoretical trend. Graphical abstract: